An Appraisal of Extension Service Delivery through Mobile Veterinary Units (MVUs) in Odisha - Jena, Anupama; Chander, Mahesh; Sinha, Sushil Kumar; Joshi, Pragya; Singh, Deepa; Thakur, Devesh (Indian Journal of Extension Education, 2020)
An ingenious way of livestock service delivery at farmersâ€™ doorstep through Mobile Veterinary Units (MVUs)Â under Rastriya Krishi Vikas Yojana (RKVY) is operational in all the 314 blocks of Odisha, with one of the objectives being to educate people on scientific livestock farming technologies. The study was conducted with a sample size of 90 farmers and 23 veterinary service providers viz., Veterinary Surgeons (VSs) and LivestockÂ Inspectors (LIs) to analyze the efficacy of extension service delivery by MVUs and farmersâ€™ demand for livestockÂ extension activities. The study concluded that, MVU professionals were very often associated with activities viz., awareness camp and home visit. Besides these, supply driven activities, input supply and trainingÂ programmes for better animal husbandry were the most needed activities by the farmers. The service providers expressed that lack of time for extension activities and unawareness of farmers about importance of extensionÂ activities, were the major problems they faced while performing extension activities.